Fabrication of Graphene Oxide and Graphene-Oxide/Peptide Biofilms: characterization, cell viability and differentiation potential of Wharton’s Jelly Mesenchymal stem cells - Puah, Perng Yang (2018)
Human Wharton’s jelly mesenchymal stem cells (WJ-MSCs) treatments are being tested clinically for a range of disorders. Surface modification techniques have been instrumental in the development of biomaterials that promote cell-surface interactions. In this study, the surface of graphene oxide (GO) was modified to promote the proliferation and differentiation of Wharton’s jelly mesenchymal stem cells (WJ-MSCs). Synthesized GO was prepared through modified Hummers method, fabrication of GO film using drop-casting method and attachment of peptide to GO film through non-covalent approach, π-π and electrostatic interactions. Synthesized GO were confirmed by UV-vis, XRD and FTIR. SEM and AFM images showed that synthesized GO has curled transparent thin film with thickness of 1.10 nm. Four peptide sequences, namely Pep1 (“N”-YIGSRWYQNMIRIKVAV-“C”), Pep2 (“N”-QHREDGSYIGSRIKVAV-“C”), Pep3 (“N”-WQPPRARIYIGSRIKVAV-“C”) and Pep4 (“N”-DGEARGDSPKRSR-“C”) were designed based short peptide sequences derived from extracellular matrix (ECM) adhesion peptides. AFM results revealed the thickness of GO biofilm (0.25 mg/mL) was 82.6 nm ± 10.4 nm, corresponding to 65 – 85 layers of single layer GO. The GO biofilm (0.25 mg/mL) treated with Pep1 shows decrease in thickness as compared to non-treated GO film and the present of peptide bond in GO/Pep biofilm was confirmed by modified Lowry method. Furthermore, GO biofilms with concentration lower than 0.25 mg/mL were able to maintain the cell viability at day 5 as compared to glass coverslip. The WJ-MSCs were able to attach and growth on GO film. Increased of cell viability at day 6 was observed for all the GO/Pep biofilms as compared to GO biofilm. GO and GO/Pep biofilm allowed WJ-MSCs attachment, proliferation and increased in osteogenic differentiation capacity. Besides, the cell cultured on GO and GO/Pep biofilm able to maintain its undifferentiated stem cell characteristic. The data obtained here collectively demonstrates that the GO/Peptide biofilm assemble via non-covalent approach is a potential substrate for the adhesion, proliferation and enhance osteogenic differentiation of human WJ-MSCs. In conclusion, GO/Pep biofilms can be utilized for designing and manipulating biomaterials for stem cell, biological and tissue engineering applications.